Estado Islâmico E Sua Opção Discursiva Pela Polêmica E A Violência (PERcursos Linguísticos, 2020)
In this article, which investigates the discursive strategies that the radical Islamic State group uses to publicize its violent actions, in the sense of establishing itself in the public space and capturing followers or volunteers, we start from the hypothesis that it uses linguistic resources such as speech prophetic / apocalypse, controversy and propaganda / incitement discourse. Our corpus was composed of texts published by the group on its social networks and gathered on the website www.jihadology.net. The research methodology we used consisted of selecting three more representative texts and studying them according to the categories of analysis that we created, considering the discursive resources that we chose. The theoretical framework considered by us was based on studies on prophecy / apocalypse made by Rabatel (2016 and 2019) and São João (1990); controversy research conducted by Amossy (2017), which included investigations by Schopenhauer (2009), Kerbrat-Orecchioni (1980), Dascal (1998) and Coser (1964, [1956], 1970); and studies on the propaganda / incitement discourse undertaken by Charaudeau (2010), Emediato (2019), Pereira (2008) and Dahlet (1996). After analyzing our corpus, we were able to confirm our hypothesis. Our expectation is that further research will be carried out to reinforce or compare the results we obtained.